Method and apparatus for slicing class hierarchies - Choi, Jong-Deok; Field, John H; Ramalingam, G.; Tip, Frank (2001)
Given a class hierarchy (a collection of classes and inheritance relations among them) and a program P that uses the hierarchy, a slice of the class hierarchy is computed with respect to the program by eliminating from the hierarchy those data members, member functions, classes, and inheritance relations that are unnecessary for ensuring that the semantics of P is maintained.